Image More to Save More - Tansy, Aaron P.; Hinman, Jason D.; Ng, Kwan L.; Calderon-Arnulphi, Mateo; Modir, Royya; Chatfield, Fiona; Liebeskind, David S. (Frontiers in Neurology, 2015)
Recent successful endovascular stroke trials have provided unequivocal support for these therapies in selected patients with large-vessel occlusive acute ischemic stroke. In this piece, we briefly review these trials and their utilization of advanced neuroimaging techniques that played a pivotal role in their success through targeted patient selection. In this context, the unique challenges and opportunity for advancement in current stroke networks’ routine delivery of care created by these trials are discussed and recommendations to change current national stroke system guidelines are proposed.